SERAPAN N, P, DAN K PADA JAGUNG MADURA-3 DI TANAH LEMPUNG LIAT BERPASIR DIAMELIORASI BIOCHAR DAN BENTONIT-TERAKTIVASI ASAM - Slamet Supriyadi; Fahmi Arief Rahman; Erick Yuhardi; Choirul Umam (Jurnal Tanah dan Sumberdaya Lahan, 2023)
Sandy clay loam soil in Bangkalan is a soil with a low content of nutrients, organic matter, bases, and cation exchange capacity (CEC), which inhibits the growth of maize plants. In addition, the nature of the soil causes the fertilizer to become more soluble, and the absorption of nutrients, especially potassium, is low. One of the efforts to increase potassium uptake in sandy loam soils is applying biochar and acid-activated bentonite. This study aimed to examine the effect of adding biochar and acid-activated bentonite to the nutrient uptake of maize plants in the sandy soil of Bangkalan. Biochar was prepared from maize cobs by the Kon-Tiki method; bentonite was activated by physical (200 oC) and chemical (1N H2SO4) methods. The greenhouse experiment was carried out using a completely randomized design with biochar (B) and acid-activated bentonite (T) as treatments, each with three levels, namely 0, 5, 10 t ha-1 and three replications. Soil analysis performed included pH, organic carbon, CEC and exchangeable bases, while plant tissue analysis included leaf height and area. The results showed that the combination of biochar and acid-activated bentonite significantly increased soil pH, soil exchangeable K, soil exchangeable Na, and leaf area of maize plants. A single application of biochar significantly increased soil organic C and maize plant height. The application of acid-activated bentonite significantly increased the CEC of sandy loam soils.